Optimization of process heat exchange in a stage drying fruit and vegetable cultures (Texas Journal of Engineering and Technology, 2025)
In work the optimization of process drying frut and vegetable of cultures is considered. The technological mode of course of process heat exchange in elementary layers of a product is certain(determined) by a method of multistage optimization. Taking into account interaction internal and external of the factors is chosen criterion of optimization of process drying fruit and vegetable of cultures.